Strategies for managing transfusional iron overload: conventional treatments and novel strategies. Issue 3 (May 2019) - Sheth, Sujit
Abstract : Purpose of review: For individuals who have transfusion-dependent anemia, iron overload is the long-term complication, which results in significant morbidity. Ameliorating this is now the biggest unmet need. This review specifically addresses this issue. Recent findings: Over the last decade or so, major advances in the treatment of these individuals, has resulted from novel strategies aimed at reducing transfusion requirement as well as optimizing chelation therapy. This review will summarize these advances and provide insights into some of the therapies in the pipeline. Strategies aimed at reducing transfusion requirement include modulation of erythropoietic regulation by reducing ineffective red cell production through activin trapping, as well as stem cell gene modification approaches, which aim for a cure, and transfusion independence. Refined means of assessing tissue iron and the introduction of oral chelators have facilitated tailoring chelation regimens with closer monitoring and improved compliance. Newer approaches to ameliorate iron toxicity have focused on the hepcidin pathway, all of which would result in increased hepcidin levels and reduction of iron absorption from the intestine, sequestration of iron in normal storage sites and reduced exposure of more susceptible organs, such as the heart and endocrine organs, to the toxic effects of increased iron. Summary: These advances offer the promise of improved management of transfusion-dependent individuals.